Penguatan nilai-nilai Pancasila melalui budaya sekolah berbasis kearifan lokal - Mustofa, Laila (Maliki Interdisciplinary Journal, 2026)
This study aims to explore how Pancasila ideas, which are reinforced through school culture based on local wisdom, impact students' character. The information was acquired through observation, interviews, and documentation as part of a descriptive qualitative approach. The findings demonstrate that when school culture is integrated with local knowledge, Pancasila values such as accountability, tolerance, religiosity, and cooperation may be internalised. By providing a framework that is close to and relevant to their daily lives, local wisdom facilitates students' understanding and application of these ideas. This approach has been effective in helping children develop their character in the face of globalization's problems, despite a number of implementation obstacles, such as a lack of comprehension and support. Thus, strengthening Pancasila values ​​through a school culture based on local wisdom is an effective strategy for developing students' character with integrity and adaptability. Therefore, ongoing support from all parties, including schools, families, and the government, is needed to ensure optimal implementation of local wisdom and meet the challenges of globalization.